Additive-induced miscibility regulation and hierarchical morphology enable 17.5% binary organic solar cells. Issue 5 (28th April 2021) - Lv, Jie; Tang, Hua; Huang, Jiaming; Yan, Cenqi; Liu, Kuan; Yang, Qianguang; Hu, Dingqin; Singh, Ranbir; Lee, Jawon; Lu, Shirong; Li, Gang; Kan, Zhipeng
Abstract : Herein, a facile and effective strategy is demonstrated to unleash the full potential of existing photoactive materials. Abstract : Due to barrierless free charge generation, low charge trapping, and high charge mobilities, the PM6:Y6 organic solar cell (OSC) achieves an excellent power conversion efficiency (PCE) of 15.7%. However, the deficient hole transfer from Y6 to PM6 limits the further enhancement of the device performance. Herein, we demonstrate an additive-induced miscibility and morphology control strategy to achieve the balance of exciton dissociation and charge collection, prompting an increase in the PCE of OSCs composed of PM6:Y6 from 15.7% to 17.5%, which stands as the top PCE value of PM6:Y6 binary OSCs. The external quantum efficiency (EQE) of the optimal device significantly improves in the wavelength range where Y6 harvests photons. Therefore, the short-circuit current density ( J SC ) was enhanced to 26.98 mA cm −2, achieving 94.4% of the maximum theoretical J SC obtained from the identical device configuration. The remarkable performance enhancement mainly results from the miscibility-driven donor and acceptor phase optimization with hierarchical morphology formation, leading to the improved photon-to-electron response of the Y6 phase, enhanced and balanced charge extraction and collection. Our findings highlight the significance of morphology control towards unleashing the full potential of OSC materials.